Design of an Inventory Information System at ITSK Soepraoen Using the Waterfall Method - Nugroho Teguh Yuono; M. Syauqi Haris; Risqy Siwi Pradini (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
In the current digital era, the use of information technology has become an urgent need for various institutions, including educational institutions. ITSK Soepraoen has integrated information systems in several units to increase operational efficiency. However, inventory data collection is still done manually using Microsoft Excel, which has proven to be less efficient and often causes delays in data processing. This research aims to design a website-based inventory information system at ITSK Soepraoen using the Waterfall method. This system is expected to facilitate data collection and management of inventory items as well as increase accuracy, transparency and efficiency in data processing. The research method used is the Waterfall approach which consists of four stages: requirements definition, system and software design, implementation, and testing. The result of this research is a lo-fi mockup of an inventory system that is well received by users with an acceptance rate of 92.75%. This percentage is relatively high so it can be concluded that the user accepts the design that has been created and for the next stage this inventory system can be fully implemented.